Family Caregiving Fostering Resilience Across the Life Course (Emerging Issues in Family and Individual Resilience,, 2018)
This comprehensive resource offers a detailed framework for fostering resilience in families caring for their older members. Its aim is to improve the quality of life for both the caregivers themselves as much as for those they support. Robust interventions are presented to guide family members through chronic and acute challenges in areas such as emotional health, physical comfort, financial aspects of care, dealing with health systems, and adjusting to transition. Examples, models, interviews, and an extended case study identify core concerns of caregiving families and avenues for nurturing positive adaptation. Throughout, contributors provide practical applications for therapists and other service providers in diverse disciplines, and for advancing family resilience as a field. Included in the coverage: Therapeutic interventions for caregiving families. Facilitating older adults' resilience through meeting nutritional needs. Improving ergonomics for the safety, comfort, and health of caregivers. Hope as a coping resource for caregiver resilience and well-being. Perspectives on navigating care transitions with individuals with dementia. Planning for and managing costs related to caregiving. Family Caregiving offers a new depth of knowledge and real-world utility to social workers, mental health professionals and practitioners, educators and researchers in the field of family resilience, as well as scholars in the intersecting disciplines of family studies, human development, psychology, sociology, social work, education, law, and medicine.